Dual-targeting CSF1R signaling attenuates neurotoxic myeloid activation and preserves photoreceptors in retinitis pigmentosa - Jiangmei Wu; Jing Zhang; Bin Lin (Journal of Neuroinflammation)
Abstract Retinitis pigmentosa (RP), a group of inherited retinal diseases characterized by progressive photoreceptor degeneration, features prominent microglial activation and monocyte-derived macrophage infiltration. While colony-stimulating factor 1 receptor (CSF1R) shows diverse roles in regulating microglial survival and behaviors in various neurodegenerative diseases, its functional significance in RP pathogenesis remains unclear. In this study, we observed upregulated CSF1R signaling specifically within disease-associated myeloid cells in the rd10 mouse model of RP. Targeted intervention via intravitreal CSF1R neutralizing antibodies and systemic PLX5622 administration achieved reduced myeloid proliferation and pro-inflammatory cytokine production and greater photoreceptor survival. Notably, CSF1R potentiation using recombinant IL-34 or CSF1 exacerbated neuroinflammation and accelerated photoreceptor degeneration. Mechanistic investigations revealed that infiltrating monocyte depletion by clodronate liposomes significantly reduced macrophage infiltration and preserved visual function. Using CX3CR1CreER/+/R26iDTR/+/rd10 mouse model, we observed that diphtheria toxin-mediated microglia ablation preserved retinal function. Overall, our findings demonstrate the prominent role of CSF1R in neurotoxic myeloid activation in the context of RP. Our results provide preclinical proof-of-concept that dual targeting of retinal and peripheral CSF1R pathways may offer a mutation-agnostic therapeutic strategy for inherited retinal degenerations.